Effect of Perceived Ease of Use, Perceived Usefulness, and Perceived Risk on Purchase Decision (A Case Study of Fashion Product to Purchase on Twitter) - Usna, Nurul (Universitas Mercu Buana, 2020)
This research aims to examine and analyze the effect of perceived ease of use, perceived usefulness, and perceived risk on purchase decision (a case study of fashion product to purchase on Twitter). The population in this research was a customer on Twitter with the criteria that have been purchased fashion product on Twitter. The sample size was taken by 150 respondents, by non-probability sampling. Data collection is done through questionnaires. An analytical technique used is the method of analysis PLS (Partial Least Square). The results showed that the ease of use variable had a positive effect on purchase decision, and the usefulness variable had a positive effect on purchase decision. And, simultaneously there is a positive effect of risk on purchase decision.